Antiviral Activity of Cynometra Cauliflora Leaves Methanolic Extract Towards Dengue Virus Type 2 - Zarina Abd Wahab, Noor; Badya, Norhidayah; Ibrahim, Nazlina; Khairul Amri Kamarudin, Mohd; Juahir, Hafizan; Ekwan Toriman, Mohd (International Journal of Engineering and Technology, 2018)
The present study is aimed at determining cytotoxicity and antiviral activities for methanolic extract obtained from leaves of Cynometra cauliflora. Cytotoxicity screening against Vero cells using MTT assay showed that the CC50 values for the extract was 36 mg/ml and the 50% Effective Concentration, EC50, was 2.19 mg/ml. The antiviral activity towards dengue virus type 2 (DENV-2) was determined using MTT method. Three treatments were used in the antiviral test; 1) post-treatment, 2) pre-treatment, and 3) virucidal. The results revealed that the post-treatment was more effective in inhibiting viral replication compared to pre-treatment and virucidal assay. The selectivity index (SI = CC50 / EC50) for the extract was 16. The findings indicated that the extract prepared from C. cauliflora was non cytotoxic to the cell with potential antiviral activity.Â Â